Dynamic Electrical Pathway Tuning in Neuromorphic Nanowire Networks - Li, Qiao; Diaz‐Alvarez, Adrian; Iguchi, Ryo; Hochstetter, Joel; Loeffler, Alon; Zhu, Ruomin; Shingaya, Yoshitaka; Kuncic, Zdenka; Uchida, Ken‐ichi; Nakayama, Tomonobu (Advanced functional materials, 2020)
Neurobiology‐inspired phenomena such as winner‐takes‐all competition and critical dynamics have been recently reported to arise in neuromorphic nanowire networks. These are unique systems where interactions between memristive elements creates emergent conductance pathways between discrete electrodes. This mode of operation can offer substantial advantages to create a truly concomitant plastic‐static system for integration in neuromorphic devices. However, critical aspects such as pathway controllability and stability are yet to be explored. In this study, pathway formation in self‐assembled neuromorphic networks formed by Ag nanowires decorated with TiO2 nanoparticles is investigated. Direct visualization of pathway formation through a neuromorphic network is attained using the lock‐in thermography technique. Using this technique, it is demonstrated that how networks preserve information from previously used pathways through increased local junction connectivity. This effect directly reshapes subsequent formation of pathways whenever the spatial location of the electrodes is dynamically changed. Combining these results with conventional current–voltage measurements, which show that the network electrically acts as a volatile switching memristor, a unique interaction between short‐term and long‐term memory arises. This produces unexpected collective dynamical states of potentiation and inhibition of network conductance whenever different spatiotemporal signals are dynamically fed to the network. Current pathway formation in neuromorphic networks is directly visualized with the lock‐in thermography technique that uses infrared sensitive camera to detect heat radiation. The network recycles parts of previously used pathways to create new ones when multiple electrodes are used. This effect is used to dynamically tune the conductance of the system by alternating voltage pulses on different electrodes.